2007
DOI: 10.1111/j.1945-5100.2007.tb00541.x
|View full text |Cite
|
Sign up to set email alerts
|

3He, 20,21,22Ne, 14C, 10Be, 26Al, and 36Cl in magnetic fractions of cosmic dust from Greenland and Antarctica

Abstract: Abstract-We report on studies of the concentrations of cosmogenic nuclides in the magnetic fraction of cosmic dust particles recovered from the South Pole Water Well (SPWW) and from Greenland. Our results confirm that cosmic dust material from these locations contains measurable amounts of cosmogenic nuclides.The Antarctic particles (and possibly those from Greenland as well) also contain minor amounts of solar Ne. Concentrations of cosmogenic nuclides are consistent with irradiation of this material as small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
0
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
(59 reference statements)
3
0
0
Order By: Relevance
“…Our study provides another substantial contribution to the debate on the survival times of small particles in space (collisional lifetimes), which are derived from dynamical models and which are shorter than their average exposure ages. While the duration required for mutual collisions to completely destroy a dust particle in space is estimated at ~2 × 10 4 yr [72,73], typical exposure ages, which are also an indicator of the lifetimes, are orders of magnitude larger with 10 5 -10 7 years [10,23,27,62,74]-a range that is in agreement with our data. This means that even by using a more complex model, we arrive at results similar to previous studies, suggesting either the collisional lifetimes need to be revised or the radionuclide data is misinterpreted [23].…”
Section: Discussionsupporting
confidence: 89%
“…Our study provides another substantial contribution to the debate on the survival times of small particles in space (collisional lifetimes), which are derived from dynamical models and which are shorter than their average exposure ages. While the duration required for mutual collisions to completely destroy a dust particle in space is estimated at ~2 × 10 4 yr [72,73], typical exposure ages, which are also an indicator of the lifetimes, are orders of magnitude larger with 10 5 -10 7 years [10,23,27,62,74]-a range that is in agreement with our data. This means that even by using a more complex model, we arrive at results similar to previous studies, suggesting either the collisional lifetimes need to be revised or the radionuclide data is misinterpreted [23].…”
Section: Discussionsupporting
confidence: 89%
“…This is within the range determined for the replicate samples (Table 1), and since the size fraction experiment had only a small component of 3 He in particles greater than 20 microns it seems unlikely that there is a very large component present in larger particle sizes in the other samples, though clearly larger particles containing extraterrestrial helium do exist (Jull et al, 2007;Osawa and Nagao, 2002;Stuart et al, 1999).…”
Section: Insert Figure 2 About Heresupporting
confidence: 79%
“…Lal and Jull (2005) also argued that large particles are important, postulating that a significant number of larger particles are formed from the atmospheric breakup of meteorites that contain 3 He produced by spallation by galactic cosmic rays. However, later work by Jull et al (2007) showed that 3 He in 50-300 micron particles from the South Pole water well (Taylor et al, 1998) is dominated by a solar wind, rather then galactic cosmic ray produced component, consistent with previous studies of micrometeorites (Stuart et al, 1999;Osawa and Nagao, 2002). Jull et al also reported cosmogenic radionuclide data for South Pole water well particles and concluded that concentrations were too low for the particles to be derived from the break-up of larger meteors.…”
Section: Size Distribution Of the Extraterrestrial Signalsupporting
confidence: 67%